Learning evaluation of the study group of Packages C programme in Sragen Regency - Junanto, Subar; Tuanaya, Rugaya; Shofa, Mila Faila; Muntaha, Muntaha; Fajrin, Latifah Permatasari (Jurnal Penelitian dan Evaluasi Pendidikan, 2024)
This study aims to evaluate the learning of the Study Group of Packages C programme in Sragen Regency. This evaluation research uses the EPPKC model, which consists of Process and Product aspects. This research uses a mixed method, a combination of quantitative and qualitative research using a descriptive approach. The evaluation subjects in this study were 322 people, including the Study Group of Packages C programme organiser, tutors, and learning citizens in the Sragen Regency. The main field trial used a sample of 84 people, while the operational field trial used a sample of 238 people. Data were collected using questionnaires, interviews, observation and documentation. Data validity techniques used source and method triangulation. The qualitative data analysis technique used in this research is an interactive analysis model, while the quantitative questionnaire results were analysed using the percentage analysis formula (percentile). The results showed that (1) the implementation of the Study Group of Packages C programme learning for the process component was included in the good category, (2) the Study Group of Packages C programme learning for the product component was included in the good category, and (3) the results of the Reviewer's Assessment of the EPPKC Instrument in the Study Group of Packages C Programme were included in the excellent category.